Fluorescence characteristics of particulate water-soluble organic compounds emitted from coal-fired boilers. (15th February 2020) - Yang, Yanrong; Qin, Juanjuan; Qi, Ting; Zhou, Xueming; Chen, Rongzhi; Tan, Jihua; Xiao, Kang; Ji, Dongsheng; He, Kebin; Chen, Xiaoting
Abstract: The fluorescence characteristics of particulate water-soluble organic compounds (WSOC) emitted by different power of coal-fired boilers (A total of 14 boilers including 1, 2, 4, 6, 10, 15, 20 tons steam per hour (t·h −1 )) in Lanzhou, an industrial city of northwest China, were analyzed by excitation-emission matrix (EEM) fluorescence spectroscopy. Results showed that the fluorescence profiles of WSOC in different power coal-fired boiler samples had certain similarities, reflecting the consistency of the fluorophore structures in the coal-originated WSOC. In general, the main excitation (Ex) and emission (Em) wavelength ranges of fluorescence peaks generated by WSOC were λEx  = 230–250 nm and λEm  = 360–430 nm. Since the fluorophore of WSOC was mainly concentrated in the fluorescent regions II and III, the main components in the fluorophore were tryptophan-like, fulvic acid and humic-like substances. Humification index (HIX), fluorescence index (FI) and freshness index (BIX) were 0.36 ± 0.36, 2.09 ± 0.42 and 1.02 ± 0.30, respectively. It may indicate that the particulate WSOC had a lower degree of humification and lower aromaticity. In the range of larger Stokes shift (λEx −1 -λEm −1  ≥ 1.2 μm −1 ), the normalized fluorescence intensity of WSOC showed the largest peak, suggesting that there may be many hydrophobic substances containing a large number of π-conjugated systems in WSOC. These findings are not only conducive to cognize the optical characteristics of particulate matter emitted from coal-fired pollution sources, but also help to consummate the spectral characteristics of coal-fired pollution sources. Graphical abstract: Image 1 Highlights: The fluorescence performance of various tons of coal-fired boilers was consistent. The peak of fluorescent organic matter were λEx  = 230–250 nm and λEm  = 360–430 nm. Water-soluble organic compounds were relatively low humification and aromaticity. The fluorescent fractions had moderate fluorophore density and molecular weight. Many hydrophobic fractions in organic matter contained rich π-conjugated systems.